PERAN ORANG TUA DALAM MEMBENTUK KARAKTER ANAK SEJAK DINI DI TK AISYIAH BUSTANUL ATHFAL V PEKANBARU - Nurhayati Nurhayati; Sariah Sariah; Nurhasanah Bakhtiar; Syafi’ah Syafi’ah; Ilmiyati Ilmiyati; Zalyana Zalyana (Kreasi: Jurnal Pengabdian Masyarakat, 2021)
Parents are the main key in the formation of children's character from an early age. The formation of early childhood character is very important because it will affect the future life, character education is an effort made by parents intentionally to develop good character (good character) based on an understanding of good and bad parents towards behavior that is objectively recognized as good for the community individuals and society. The activity aims to increase the understanding of teachers and parents at Aisyiah Bustanul Athfal V Kindergarten Pekanbaru in terms of character education for early childhood and efforts to choose the right parenting pattern in the formation of children's character. The method of activity carried out is participatory, namely an effort to provide information to parents and teachers so that there is an understanding and increased understanding of the material presented and parents and teachers play a role both in the process and implementation of activities. The form of service activities are counseling and interactive discussions with the results of the activities, namely the achievement of the target number of training participants 72% or can be considered good, the achievement of the material targets that have been planned for the activity with a percentage (80%) and the ability of participants seen from the mastery of the material can be assessed as good (80 %). This can be seen from the ability of the teachers and parents to answer the reflections given by the instructor.